Modeling language change across the lifespan: Individual trajectories in community change. (17th June 2016) - Baxter, Gareth; Croft, William
Abstract: We use a mathematical model to examine three phenomena involving language change across the lifespan: the apparent time construct, the adolescent peak, and two different patterns of individual change. The apparent time construct is attributed to a decline in flexibility toward language change over one's lifetime; this explanation is borne out in our model. The adolescent peak has been explained by social networks: children interact more with caregivers a generation older until later childhood and adolescence. We find that the peak also occurs with many other network structures, so the peak is not specifically due to caregiver interaction. The two patterns of individual change are one in which most individuals change gradually, following the mean of community change, and another in which most individuals have more categorical behavior and change rapidly if they change at all. Our model suggests that they represent different balances between the differential weighting of competing variants and degree of accommodation to other speakers.